Dynamics of rising bubbles and stress measurements through birefringence in viscoelastic liquids - Eribol, Pınar. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
Bubble dynamics in a viscoelastic liquid are studied to check the existence of a discontinuity in the terminal velocity that occurs at some critical bubble volume and cusp formation at the bubble tail and their relation with the stress around the bub ble, which is measured through flow birefringence. A wide range of bubble volumes, 5-2000 mm3 in 0.10-0.40 wt% polyacrylamide (PAAM) solutions is employed. The terminal velocity decreases with PAAM concentration and increases with bubble vol ume but plateaus. The plateau velocity is independent of PAAM concentration. No discontinuity in the terminal velocity is observed, which is supported by the bubble shape parameters of which circularity, the minor axis, and eccentricities are found to be concentration-dependent. Increasing the bubble volume changes the shape from spher ical to prolate, teardrop with a cusp and cap-shapes. The critical bubble volume for the cusp formation is independent of the PAAM concentration. With the addition of 100 ppm surfactant SDS leads less distortion of the bubbles and cusp formation at smaller volumes. Large bubbles and dilute solutions cause bubbles wobbling. Increasing the PAAM and the surfactant concentrations shows an increase in the lateral direction motion. The retardance and the stretching angle around the bubble are measured for PAAM and hydroxypropyl cellulose (HPC) solution. For small bubbles, the stress is proportional to the concentration; whereas for large ones, bubble shapes become im portant for the stress. No significant effect of the temperature gradient on the bubble dynamics is observed. Weak convection patterns are seen through Schlieren method.
Keywords: Viscoelastic materials.